Fabrication of cyclic olefin copolymer (COC/TOPAS) microfluidic devices: hot embossing and thermal bonding - Jena, Rajeeb Kumar (2014)
Amorphous cyclic olefin copolymers (COCs) have been widely used for fabricating microfluidic devices using hot embossing technique followed by thermal bonding with a cover plate. However, optimal manufacturing process conditions for both hot embossing and sealing by thermal bonding will only be possible if the COCs thermo-mechanical behavior is experimentally well characterized, mathematically modeled, and implemented in a numerical simulation. We have conducted large-strain compression experiments of COCs in a wide temperature and strain rate range. The constitutive theory and numerical implementation developed by Srivastava et al. (2010) were applied to model the behavior of COCs. We have employed their numerical implementation, together with the material parameters for COCs determined here, to predict the response of COCs in micro-scale hot embossing followed by sealing by thermal bonding. Finally, an important permanent surface modification technique (photografting) was used so that the COC microfluidic substrates could be thermally sealed to enhance their bond strength without affecting the channel integrity.